The Demand Cor International Reserves and their Opportunity Cost. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
An empirical study that shows that countries' reserve holdings are sensitive to the rates at which they can borrow on international financial markets, this analysis confirms the view that holding major currencies as reserve assets has costs that are frequently unrecognized. Between 1978-82 for 24 sample countries, and between 1978-86 for the same sample less those countries with debt-servicing difficulties, international borrowing costs were found to be a highly significant determinant of reserve holdings-particularly before 1982 for the group with debt difficulties.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet